Abnormalities of the Ventilatory Equivalent for Carbon Dioxide in Patients with Chronic Heart Failure - Lee Ingle; Rebecca Sloan; Sean Carroll; Kevin Goode; John G. Cleland; Andrew L. Clark (Pulmonary Medicine)
Introduction. The relation between minute ventilation (VE) and carbon dioxide production (VCO2) can be characterised by the instantaneous ratio of ventilation to carbon dioxide production, the ventilatory equivalent for CO2 (VEqCO2). We hypothesised that the time taken to achieve the lowest VEqCO2 (time to VEqCO2 nadir) may be a prognostic marker in patients with chronic heart failure (CHF). Methods. Patients and healthy controls underwent a symptom-limited, cardiopulmonary exercise test (CPET) on a treadmill to volitional exhaustion. Results. 423 patients with CHF (mean age 63±12 years; 80% males) and 78 healthy controls (62% males; age 61±11 years) were recruited. Time to VEqCO2 nadir was shorter in patients than controls (327±204 s versus 514±187 s; 𝑃=0.0001). Univariable predictors of all-cause mortality included peak oxygen uptake (𝑋2=53.0), VEqCO2 nadir (𝑋2=47.9), and time to VEqCO2 nadir (𝑋2=24.0). In an adjusted Cox multivariable proportional hazards model, peak oxygen uptake (𝑋2=16.7) and VEqCO2 nadir (𝑋2=17.9) were the most significant independent predictors of all-cause mortality. Conclusion. The time to VEqCO2 nadir was shorter in patients with CHF than in normal subjects and was a predictor of subsequent mortality.